Abelian theorems for transformable Boehmians - Dennis Nemzer (International Journal of Mathematics and Mathematical Sciences)
A class of generalized functions called transformable Boehmians contains a proper subspace that can be identified with the class of Laplace transformable distributions. In this note, we establish some Abelian theorems for transformable Boehmians.